Ten year follow-up of pyrocarbon implants for proximal interphalangeal joint replacement. (July 2014) - Reissner, L.; Schindele, S.; Hensler, S.; Marks, M.; Herren, D. B.
Results of anatomical resurfacing of the proximal interphalangeal joint using pyrocarbon implants showed reasonable clinical results with a high radiographic migration rate. The aim was to investigate the subjective, clinical, and radiographic results 10 years following surgery, and to compare them with our 2-year follow-up data. We re-evaluated 12 patients with 15 proximal interphalangeal implants on average 9.7 years after surgery. Pain significantly improved from 7.6 on a visual analogue scale pre-operatively to 1.4 at 2 years, and to 0.7 at the final follow-up. The mean total range of motion in all replaced joints was 36° pre-operatively and 39° at the 2-year follow-up, but had decreased significantly to 29° at 10 years. We saw one implant migration in addition to the eight migrated implants we already found 2 years after surgery. The moderate clinical results, combined with the high migration rate, mean that we no longer use this kind of implant.